THE EFFECT MODEL TO LEARN GUIDED DISCOVERY LEARNING ON THE RESULT STUDY OF MATHEMATIC IN STUDENTS CLASS VII SMP N 2 KEPENUHAN ON MATTER RECTANGLE AND TRIANGLE - -, Firdaus; Deswita, Hera; -, Arcat (Jurnal Ilmiah Mahasiswa FKIP Prodi Matematika, 2015)
The purpose of research was to know the effect model guided discovery learning in result of mathematic learning in students grade VII SMP N 2 Kepenuhan in matter rectangle and triangle. Take sample used sample jenuh Population in this research is all of students grade VIIA as the class exsperimental that is 22 students and students grade VIIB as the class control that is 23 students. The study was exsperiment research. Instrument of this research to collect the data are students result test by using objective test. Instrumentation test are validity, reliability, layer terrace difficult, and capacity difference. The test normality by using liliefors test and test homogenity use F test that stage of value 0,05. The data students result from final test and analysis statistic is by using thitung = 2,18 dan ttabel= 2,02 so H1 received.